ANALISIS EFEKTIVITAS PROGRAM USAHA AGRIBISNIS PERDESAAN (PUAP) SERTA DAMPAKNYA TERHADAP TINGKAT PENDAPATAN PETANI (STUDI KASUS PADA GABUNGAN KELOMPOK TANI TELUK JAYA) - Yudi Triyanto (JURNAL AGROPLASMA, 2014)
Study the effectivity analysis of Program Usaha Agribisnis Perdesaan (PUAP) and its impact on farmer income levels (case study of the Teluk Jaya Farmers Group Association) aims to 1. knowing how large the effectivity of PUAP funds is for income levels in poverty alleviation in Teluk Desa Sentosa Panai Hulu Subdistrict, 2. to analyze and determine the level of income of Gapoktan Teluk Jaya Farming Business in Teluk Sentosa, Panai Hulu Subdistrict before and after receiving PUAP assistance. The results showed that the effectivity of PUAP program funding is very effective and good, it can be seen from the results of the F test of 12.406 with a significant level of 0.000 while the F value of the table is 2.051. When compared to the value of F test (12.406) > Ftable (2.051) at α 5%, it was concluded that simultaneously the effectivity variable and the PUAP program had a positive effect. The increase in income of the Teluk Jaya Farmers Group in Teluk Sentosa after receiving PUAP funds can be known from the t table for the effectivity variable of 2.663 and the PUAP program for 1.270 with a significant value for each independent variable (2.051); (0.073). Whereas for the t table value in the distribution statistics t table with the level of test α = 5% and df1 = 27 of 2,051. Based on the criteria that if the value is t count> t table); namely (2.663> 2,051) (1,270> 2,051) so that it can be concluded that the effectivity variable partially has a positive and significant effect on the income level.Keywords : effectivity variable,  income level, PUAP program